Analysis of the operating mechanism and parameter optimization of the upright conveying device for reed harvesters - Huang, Jicheng; Zhang, Bin; Tian, Kunpeng; Mu, Senlin; Kong, Fanting; Mu, Zhongqiu; Shen, Weijie; Shen, Cheng (International Journal of Agricultural and Biological Engineering, 2025)
To investigate the operational mechanism and quality improvement strategies of a reed upright conveying device, first, the structural design was completed, and a force analysis of the conveying process was conducted. A rigid-flexible coupling simulation model of reed stalks and the conveying mechanism was then employed to examine the effects of the structural parameters of the conveying chain links on the maximum contact force exerted on the reed stalks and to identify the optimal parameter combination. High-speed photography experiments were carried out during the conveying process to capture the motion states and trajectories of the reed stalks, elucidating the causes of stalk breakage and blockages. Subsequently, response surface experiments were conducted to investigate the primary factors influencing upright conveying quality. Mathematical models for predicting damage rate and conveying rate were established, and the effects of various factors on these indicators were analyzed. Multi-objective optimization of the regression models was performed based on practical production requirements, yielding an optimal parameter combination: transverse conveying speed of the chain at 1.1 m/s, speed ratio of 1.2, and upper conveying chain position at 1.37 m. Experimental results indicated a damage rate of 11.90% and a conveying rate of 95.11%, meeting the operational requirements for mechanized reed harvesting and conveying. These findings provide fundamental theoretical data for the development of reed harvester conveying components and the selection of operational parameters.Keywords: reed harvester, upright conveying device, operating mechanism analysis, parameter optimization, high-speed photographyDOI: 10.25165/j.ijabe.20251803.9704Citation: Huang J C, Zhang B, Tian K P, Mu S L, Kong F T, Mu Z Q, et al. Analysis of the operating mechanism and parameter optimization of the upright conveying device for reed harvesters. Int J Agric & Biol Eng, 2025; 18(3): 135–144.